Removal of concentrated sulfamethazine by acclimatized aerobic sludge and possible metabolic products - Yang, Na (2015)
This article examined the biological removal of high concentrated sulfamethazine (SMZ) antibiotics by the acclimatized activated sludge in lab-scale SBRs system. The removal of SMZ was characterized by a quick adsorption and a slow process of biodegradation. The adsorption capacity of activated sludge for SMZ was 44 and 47 µg SMZ/g SS, respectively, with the initial SMZ concentrations of 1 and 2 mg/L. The adsorption process fitted pseudo-second-order kinetic model. In a series of batch studies, with the increase of initial SMZ concentration that were 1, 2, 3, 5, 7 and 9 mg/L, 56.0%, 51.3%, 42.2%, 29.5%, 25.0% and 20.8% of influent SMZ were biodegraded within 24 h of biological reaction, respectively. The Monod equation applied to simulate SMZ biodegradation had a good coefficient of determination (R2 > 0.99). Furthermore, the results of HPLC demonstrated that the SMZ was not completely removed by the acclimatized activated sludge. From the analysis of LC-MS, 4 intermediates of SMZ biodegradation were identified: Sulfanilic Acid, 4-amino-N-(4,6-dimethyl-2 pyrimidin) benzene sulfonamide, N-(4,6-dimethyl-2-pyrimidin)-4-N-(benzene sulfonamide) benzene sulfonamide, N-(4,6-dimethyl-2-pyrimidin)-4-N-(4,6-dimethyl pyrimidine) benzene sulfonamide, and N-(4,6-dimethyl-2-pyrimidin)-4-N-(3-dimethyl-4-N sodium benzene sulfonamide) benzene sulfonamide.